N-terminal acetylation: an essential protein modification emerges as an important regulator of stress responses. (26th June 2018) - Linster, Eric; Wirtz, Markus
Abstract : In this review, we summarize the current knowledge on the NAT machinery in higher plants and discuss the potential function of NTA during biotic and abiotic stresses. Abstract: N-terminal acetylation (NTA) is a prevalent protein modification in eukaryotes. The majority of proteins are acetylated at their N-terminus in a co-translational manner by ribosome-associated N-terminal acetyltransferases (NATs). However, the recent discovery of Golgi membrane-localized NATs in metazoa, and plastid-localized NATs in plants challenged the dogma of static, co-translational imprinting of the proteome by NTA. Indeed, NTA by the cytosolic NatA is highly dynamic and under hormonal control in plants. Such active control has not been evidenced yet in other eukaryotes and might be an adaptation to the sessile lifestyle of plants forcing them to cope with diverse environmental challenges. The function of NTAs for individual proteins is distinct and yet unpredictable. In yeast and humans, NTA has been shown to affect protein–protein interactions, subcellular localization, folding, aggregation, or degradation of a handful of proteins. In particular, the impact of NTA on the protein turnover is documented by diverse examples in yeast. Consequently, NTA was recently dicovered to be a degradation signal in a distinct branch of the N-end rule pathway, ubiquitin-mediated proteolysis. In this review, we summarize the current knowledge on the NAT machinery in higher plants and discuss the potential function of NTA during biotic and abiotic stresses.